The Effects of Plastifications on Vibration Characteristics and Stability - LAROUZI, ABDUL AZIZ EIN (İstanbul Kültür Üniversitesi, 2025)
This thesis presents a comparative study examining the capacity curves of a reinforced concrete two-dimensional structure, as well as various free vibration parameters, including the fundamental period and mode shapes, while accounting for stability loads (second-order effects). The analyzed frame is derived from a reinforced concrete building with three bays in the x-direction, five bays in the y-direction, and five stories. The building was designed in accordance with TS500 and TBDY2018 standards. The capacity curves were obtained under four different lateral force distributions: based on story mass and absolute elevation, first mode shape, single-mode modal contribution, and two-mode modal participation, utilizing ETABS software. Free vibration analysis was conducted at each hinge occurrence. In all four cases, the fundamental period generally increased with each hinge occurrence, whereas the stability load parameter decreased progressively until reaching zero at failure. The participation factors did not exhibit significant changes throughout the analysis. Among the force distributions, the method based on story mass and absolute elevation demonstrated the largest shift in mode shapes. The distributions based on the first mode shape and single-mode modal contribution produced similar results, while the two-mode modal contribution force distribution showed a notable shift: to one side in the lower stories and to the opposite side in the higher stories. Furthermore, the safety factor against buckling exhibited a more pronounced depreciation compared to the increase in the lateral load parameter, potentially leading to early failure due to buckling force.
Keywords: Free Vibration Analysis; Mode Shapes; Plastic Hinges; Pushover Analysis; Seismic Performance; Lateral Load Distribution